Reflected Appraisals dan Mathematic Academic Self-Efficacy pada Siswa SMA - Tansil, Sampurna; Aditomo, Anindito; Tjahjono, Evy (Faculty of Psychology, Universitas Surabaya, 2009)
This study examined the relationship between reflected appraisal from significant others (mother, father, peers, and teachers) and students’ academic self efficacy in mathematics. Reflected appraisal is an individual’s perception about how other people evaluate him/her. Subjects for this study were students (age 16-18) from year 12 taking a science major at a Catholic high school in Surabaya (N = 241). Results indicate that reflected appraisal significantly predicts self-efficacy (R = 0.44; p<0.05). This means that students who feel they are evaluated positively by their parents, teachers, and friends, tend to have high self-efficacy scores. Penelitian ini bertujuan melihat kaitan antara reflected appraisals oleh orang-orang terdekat (ibu, ayah, teman, dan guru) terhadap self-efficacy akademis siswa dalam bidang matematika. Reflected appraisal adalah persepsi seseorang mengenai bagaimana orang lain menilai kemampuan dirinya. Subjek penelitian adalah siswa-siswi kelas 12 jurusan IPA salah satu SMA Katolik swasta di Surabaya berusia 16-18 tahun (N = 241). Hasil penelitian menunjukkan bahwa reflected appraisals secara signifikan memprediksi self-efficacy akademik di bidang matematika (R =0.44; p < 0.05 ). Artinya, seseorang yang merasa dipandang positif oleh orang tua, guru, dan temannya cenderung memiliki self-efficacy matematika yang tinggi pula.